Human Resources Development Strategy and its Role in Promoting Employees Strategic Thinking Competencies: A Study at Jordanian Information Technology Companies - Bakir, Sahar Moh’d Abu (European Scientific Journal, ESJ, 2019)
This study aimed to explore the role of human resources development strategy (training, development and learning programs) in promoting employees strategic thinking competencies at the Jordanian (IT) companies. Recently these companies are confronting unprecedented competition; the number of organizations that are offering similar (IT) services is increasing in the Jordanian market; consequently the need for highly skilled innovative employees is essential to maximize the benefits of future opportunities and avoiding threats. It was proved through strategic management research that strategic thinking is the corner stone in successful strategic planning; strategic thinkers represented the inimitable competitive advantage. Accordingly based on the analytical quantitative methodology this study evaluated the role of Jordanian (IT) companies’ endeavors in promoting employees’ strategic thinking competencies. 140 companies participated in the survey, and from each company human resources and operations managers were selected to fill the study’s questionnaire, the results of the study implied that the surveyed companies are engaged in formulating and implementing development strategy’s three programs, and there is a statistically significant relationship and impact of development and learning programs on enhancing strategic thinking competencies. Meanwhile the training programs have nonstatistically relationship or impact on enhancing employees’ strategic thinking competencies. Moreover the study’s results revealed that the newly graduate employees lacked strategic thinking competencies. Relying on the study’s results it was recommended modifying the content of training programs, and to induce the strategic thinking competencies within the main (IT) courses at the Jordanian Universities.